2021
DOI: 10.17049/ataunihem.780825
|View full text |Cite
|
Sign up to set email alerts
|

Kanser Etki̇nli̇ği̇ne Katilan Bi̇reyleri̇n Kansere İli̇şki̇n Tutumlarinin Beli̇rlenmesi̇

Abstract: Determining the Attitude of IndividualsAttending the Cancer ActivityAim: This study was conducted to determine the attitude of the society towards cancer. Method:The data of the descriptive study were collected at the World CancerDay event on February 4, 2019. The universe of the study consists of individuals over the age of 18 who participate in cancer activity. It is aimed to reach the entire universe by not choosing the sample. The data were collected using a personal information form and "Attitude Scale To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Our study also found that the social well-being level was high in patients with low educational levels (primary school education and below group) and those living alone. Kuralay et al (2021) showed that the attitudes of patients toward cancer were negatively affected in those patients with a higher education level (Kuralay et al, 2021). A higher level of social wellbeing in patients with lower education levels may be related to the patient's perception of health and illness, their response to illness and treatment and adaptation to the process; morever this group of patients can focus their attention on the social environment more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that the social well-being level was high in patients with low educational levels (primary school education and below group) and those living alone. Kuralay et al (2021) showed that the attitudes of patients toward cancer were negatively affected in those patients with a higher education level (Kuralay et al, 2021). A higher level of social wellbeing in patients with lower education levels may be related to the patient's perception of health and illness, their response to illness and treatment and adaptation to the process; morever this group of patients can focus their attention on the social environment more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that the social well-being level was high in patients with low educational levels (primary school education and below group) and those living alone. Kuralay et al (2021) showed that the attitudes of patients toward cancer were negatively affected in those patients with a higher education level [39]. A higher level of social well-being in patients with lower education levels may be related to the patient's perception of health and illness, their response to illness and treatment and adaptation to the process; morever this group of patients can focus their attention on the social environment more easily.…”
Section: Discussionmentioning
confidence: 99%
“…'nın (18) çalışmasında, kadınların APTÖ toplam puan ortalamaları 130,72±26,10, Apay ve ark. 'nın (17) çalışmasında ise 114,11±0,91 olarak bulunmuştur. Literatürdeki çalışmalara göre araştırmadan elde edilen puan ortalamasının düşük olmasının, çalışmaların ülkemizin faklı bölgelerinde ve farklı örneklem gruplarındaki kadınlar ile yürütülmüş olması ile ilişkili olabileceği düşünülmektedir.…”
Section: Discussionunclassified
“…Ayrıca ilköğretim ve altı mezunu, geliri giderinden az, geniş aile yapısına sahip ve eşinin eğitim durumu ilköğretim ve altı olan, dört ve üzeri çocuk sahibi olan, vajinal doğum yapmış ve daha önce AP yöntemi kullanmamış olan kadınların aile planlamasına ilişkin tutumlarının daha olumlu olduğu bulunmuştur. Konu ile ilgili yürütülmüş olan çalışmalarda da benzer sonuçlar elde edilmiştir (9,17,18) . Elde edilen sonuçlar çalışmanın, büyükşehirde yürütülmüş olması, genellikle evlilik yaşının geç olması, buna bağlı olarak ileri yaş gebeliklerinin daha yüksek oranda olması ile ilişkilendirilebilinir.…”
Section: Discussionunclassified